2016
DOI: 10.21123/bsj.2016.13.2.0253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some induce chemical and biological agents against (Tilletia tritici (Bjerk) and T.laevis (Kühn) causal agents of wheat Common bunt disease

Abstract: In this study, a total of 209 individuals of leeches were collected from Al-Hindyia River / Babil Province. 116 individuals were identified as Erpobdella octaculata (Linnaeus, 1758), 50 individuals as Erpobdella punctata (Leidy,1870) and 43 individuals as Hemiclepsis marginata (Müller, 1774). Four samples were collected monthly during a period from February to June 2018. Some physical and chemical water properties were also examined, including air and water temperature, potential of hydrogen pH, Electrical Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies on alternative and eco-friendly control methods of common bunt have mainly focused on different seed treatments, e.g. with plant extracts from Cannabis sativa , Eucalyptus globulus , Thuja sinensis and Datura stramonium , cereal flour, milk powder and other organic compounds, hot water, hot air treatments and antagonistic bacteria and fungi, achieving good results in controlling the disease ( Singh et al., 1979 ; Borgen et al., 1995 ; El-Naimi et al., 2000 ; Shams-Allah et al., 2016 ). Oil application on seeds deserves deep attention, as different treatments may give different results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on alternative and eco-friendly control methods of common bunt have mainly focused on different seed treatments, e.g. with plant extracts from Cannabis sativa , Eucalyptus globulus , Thuja sinensis and Datura stramonium , cereal flour, milk powder and other organic compounds, hot water, hot air treatments and antagonistic bacteria and fungi, achieving good results in controlling the disease ( Singh et al., 1979 ; Borgen et al., 1995 ; El-Naimi et al., 2000 ; Shams-Allah et al., 2016 ). Oil application on seeds deserves deep attention, as different treatments may give different results.…”
Section: Discussionmentioning
confidence: 99%
“…They ranged from sensitive to resistant varieties. According to [ 7 ] The studied varieties were divided depending on the rate of its infection by disease of the covered smut into three main categories:The first section is the varieties that resisted the disease and it included the cultivar Croplus, which recorded a significant superiority so it showed high resistance to the disease so percentage of the infection reached 5.26%. The second section is the varieties same the medium-resistant, which included the Torus variety reached the percentage of the infection with the disease was 23.8%.…”
Section: Response Of Some the Wheat Varieties To The Infection By Dis...mentioning
confidence: 99%
“…so concentration of the phenols in them reached (67, 78, 85, 89 and 98) mg gm-1 on respectively without of the pathogen, and cultivar of the Taurus recorded highest of concentration of the phenols in presence of the pathogen was 115 mg gm-1. That high concentration of the phenols is an indicator of effectiveness of the plant's defense mechanisms in resisting pathogens,and showed [ 12 ] that the phenolic substances are produced and accumulated in the plant increase from the plant's resistance to the fungal pathogens, and [ 7 ] That reduction in the incidence of disease of the covered smut accompanied by an increase in accumulation of the phenolic substances, which is one of the defense means to combat the pathogen. Results of table (2) showed that the varieties all them with the presence of the pathogen Croplus, Wafaia, Adnah, IPA 99, and Taurus so content of the peroxidase reached (268, 276, 295, 305, and 326) min gm-1on respectively were significantly superior with same of the varieties without the presence of the pathogen Adnah, Wafaia, Croplus, Iba99 and Taurus, so content of the chlorophyll in them reached (249, 251, 256, 259, and 309) min gm-1 respectively, without the pathogen.That content of enzyme the of peroxidase plays a role in resisting of the pathogens from through the association with hydrogen peroxide which works to destroy enzyme of the pectinase present in wall of the cell of the fungal pathogens.…”
Section: The Effect Of the Infection By Disease Of The Covered Smut O...mentioning
confidence: 99%